2022
DOI: 10.3390/cells11121950
|View full text |Cite
|
Sign up to set email alerts
|

Current and Novel Therapeutic Approaches for Treatment of Diabetic Macular Edema

Abstract: Diabetic macular edema (DME) is a major ocular complication of diabetes mellitus (DM), leading to significant visual impairment. DME’s pathogenesis is multifactorial. Focal edema tends to occur when primary metabolic abnormalities lead to a persistent hyperglycemic state, causing the development of microaneurysms, often with extravascular lipoprotein in a circinate pattern around the focal leakage. On the other hand, diffusion edema is due to a generalized breakdown of the inner blood–retinal barrier, leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 159 publications
0
39
0
Order By: Relevance
“…Their benefit is that steroids can be safely used during pregnancy, contrary to anti-VEGF drugs. In addition to the intravitreal injections of triamcinolone, the currently used biodegradable intravitreal implants of dexamethasone and fluocinolone ensure a slow release of those steroids over 4 and 36 months, respectively [ 101 ].…”
Section: Advances In the Treatment Of Namd And Dmementioning
confidence: 99%
“…Their benefit is that steroids can be safely used during pregnancy, contrary to anti-VEGF drugs. In addition to the intravitreal injections of triamcinolone, the currently used biodegradable intravitreal implants of dexamethasone and fluocinolone ensure a slow release of those steroids over 4 and 36 months, respectively [ 101 ].…”
Section: Advances In the Treatment Of Namd And Dmementioning
confidence: 99%
“…Monthly, then bimonthly, then as needed, or treat and extend [2,10,39] Once [15] Close follow-up Extended monthly 58.3% have ongoing treatment at 10 years [50] As needed…”
Section: Intensitymentioning
confidence: 99%
“…+++ [6,10] + [9] Endophthalmitis + (rare) [2] No Thromboembolic events + (rare) [2] No Abbreviations: PRRR, peripheral panretinal photocoagulation; nAMD, neovascular age-related macular degeneration; VEGF, vascular endothelial growth factor; OCT, optical coherence tomography.…”
Section: Intensitymentioning
confidence: 99%
“…Studies have shown that it is significantly lower macular thickness, improving visual activity (Rodríguez et al, 2019). Previous studies have analyzed the impacts of different doses of TA on DME (Abdel-Maboud et al, 2021;Chauhan et al, 2022). However, few studies have been conducted on comparative analysis of various doses of TA.…”
Section: Introductionmentioning
confidence: 99%